A Semiotic Analysis of Denotative and Connotative Meanings in The Hustle Movie - Hosiana Dominggus; Ansor Putra; Neil Amstrong (ELITE: Journal of English Language and Literature, 2025)
The research discusses the denotative and connotative meanings in the movie The Hustle, based on Barthes’s theory. The objective of this research is to describe how denotative and connotative meanings are conveyed in the film The Hustle, utilizing Barthes’s theory. To support the research, the researcher adds additional theory retrieved from Dickins (2019) to identify the types of connotative meanings that appear. The descriptive qualitative method is used in this study. The source of data is based on the Hustle movie. The data was gathered by downloading, watching, reading, identifying, and coding. The data were analyzed by presenting, describing, interpreting, and concluding the data analysis results. As a result of the analysis, it can be concluded that in the Hustle movie, denotation describes the literal meaning of the things the researcher found in this movie, and connotation describes the underlying, deeper messages. The use of denotation and connotation words reveals the characters’ traits, indicating that Penny’s personality is that of a casual person. In contrast, Josephine’s personality is more formal, preferring to speak correctly. The researcher also found that the Hustle movie features several scenes that perpetuate stereotypes. The picture illustrates a stereotype prevalent in a particular country. Messages or feelings that a film evokes cause the movie’s audience to experience a range of emotions while watching it.